2007
DOI: 10.1017/s003329170700997x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow changes during retrieval of traumatic memories before and after psychotherapy: a SPECT study

Abstract: Neural mechanisms involved in subthreshold PTSD may share neural similarities with those underlying the fragmented and non-verbal nature of traumatic memories in full PTSD. Moreover, psychotherapy may influence the development of a narrative pattern overlaying the declarative memory neural substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0
19

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 36 publications
2
113
0
19
Order By: Relevance
“…For example, in a sample of subthreshold PTSD patients who were compared with matched waiting-list subthreshold PTSD patients, a course of exposure-based and cognitive restructuring therapy led to significantly higher levels of CBF in the parietal lobes, left hippocampus, thalamus and left prefrontal cortex during memory retrieval after psychotherapy. 72 In addition, the effects of eye movement desensitization and reprocessing therapy on CBF in a group of PTSD patients listening to a traumatic script showed that a significant tracer difference present before treatment in the uncus (BA 36) disappeared after treatment, while a significant difference appeared in the lateral temporal pole (BA 21). 73 Furthermore, in a group of 8 patients with PTSD, imaginal exposure and cognitive restructuring was associated with increased activation in the rostral anterior cingulate cortex, 74 and improvements in PTSD symptom severity were correlated with increased rostral anterior cingulate activation and decreased amygdala activation.…”
Section: Should Neuroimaging Studies Include Ptsd Patients Receiving mentioning
confidence: 99%
“…For example, in a sample of subthreshold PTSD patients who were compared with matched waiting-list subthreshold PTSD patients, a course of exposure-based and cognitive restructuring therapy led to significantly higher levels of CBF in the parietal lobes, left hippocampus, thalamus and left prefrontal cortex during memory retrieval after psychotherapy. 72 In addition, the effects of eye movement desensitization and reprocessing therapy on CBF in a group of PTSD patients listening to a traumatic script showed that a significant tracer difference present before treatment in the uncus (BA 36) disappeared after treatment, while a significant difference appeared in the lateral temporal pole (BA 21). 73 Furthermore, in a group of 8 patients with PTSD, imaginal exposure and cognitive restructuring was associated with increased activation in the rostral anterior cingulate cortex, 74 and improvements in PTSD symptom severity were correlated with increased rostral anterior cingulate activation and decreased amygdala activation.…”
Section: Should Neuroimaging Studies Include Ptsd Patients Receiving mentioning
confidence: 99%
“…O uso da reestruturação cognitiva é considerado uma opção eficaz em casos de fobia social (D'el Rey e Pacini, 2006), homens perpetuadores de violência doméstica (Norman e Ryan, 2008), raiva (Deffenbacher et al, 2000;Whiteman et al, 1987), TEPT (Bryant et al, 2008;Peres et al, 2007), dependência de tabaco (Shobola, 2007), compras compulsivas (Filomensky e Tavares, 2009) e regulação da emoção como em fobias e transtorno de ansiedade (Porto et al, 2008).…”
Section: Processo De Reestruturação Cognitivaunclassified
“…Concentrações mais elevadas dessa substância antes do início do tratamento estão relacionadas com maior redução dos sintomas após a terapia (Zurowski et al, 2012). Peres et al (2007) analisaram a estrutura neural antes e depois da psicoterapia, através de SPECT, em dezesseis indivíduos que vivenciaram situações traumáticas, mas não apresentavam todos os critérios necessários para o diagnóstico de TEPT. Após quinze sessões de psicoterapia, utilizando a exposição e a reestruturação cognitiva, foi observado que, comparado ao grupo-controle, que apresentava as mesmas características do grupo experimental, mas que, ao invés de receber tratamento, aguardou em lista de espera, os sujeitos submetidos à psicoterapia, apresentaram aumento na atividade do córtex pré-frontal esquerdo, no hipocampo esquerdo e no lobo parietal após a psicoterapia.…”
Section: Evidências De Modifi Cações Neuroanatômicas E Funcionais No unclassified
See 1 more Smart Citation
“…[33] Bu bulgu anksiyete bozukluğu ve depresyonu olanlarda antidepresan tedavisi ile amigdala aktivitesindeki azalma bilgisi ile örtüşmektedir. [43][44][45] Amigdaladaki serotonerjik inervasyonların serotonerjik genler tarafından dü-zenlendiği; TPH2 polimorfizminin anksiyete belirtileri ile ilişkili olduğu ve bu ilişkinin amigdala aktivasyonu değişikliği ile irtibatlı olduğu bildirilmiş-tir. [33,46,47] TPH2 polimorfizmin nöronal ve davranışsal plasebo yanıtı ile ilişkili olduğu gösterilmiştir.…”
Section: Anksiyete Ve Plasebounclassified